SENTIMENT ANALYSIS BASED ON TWITTER DATA ON VIOLENCE - Jumhare, Nihal; G, Raja Rajeswari; Jayakrishnan, Balaji (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Due to the large volume of opinion-rich web resources such as Twitter, Facebook, blogs, and news available in digital form, and much of the current research is focusing on the area of sentiment analysis using text analysis. People are getting attracted to develop a system that can extract opinions based on their response on social media sites. Algorithms can be developed so as to predict preferences of people to improve economic and marketing research. This paper presents a sentiment analysis on a recent scenario of Uri Attack.